Evidence of Influenza A(H5N1) Spillover Infections in Horses, Mongolia - Batchuluun Damdinjav; Savitha Raveendran; Laura Mojsiejczuk; Ulaankhuu Ankhanbaatar; Jiayun Yang; Jean-Remy Sadeyen; Munir Iqbal; Daniel R. Perez; Daniela S. Rajao; Andrew Park; Mafalda Viana; Pablo R. Murcia (Emerging Infectious Diseases)
Recent outbreaks of influenza A(H5N1) have affected many mammal species. We report serologic evidence of H5N1 virus infection in horses in Mongolia. Because H3N8 equine influenza virus is endemic in many countries, horses should be monitored to prevent reassortment between equine and avian influenza viruses with unknown consequences.